2014
DOI: 10.3390/ijerph110505251
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Presence of 13 Active Compounds in Surface Water Collected from Rural Areas in Northwestern Spain

Abstract: Drug residues are considered environmental contaminants, and their occurrence has recently become a matter of concern. Analytical methods and monitoring systems are therefore required to control the continuous input of these drug residues into the environment. This article presents a suitable HPLC-ESI-MS/MS method for the simultaneous extraction, detection and quantification of residues of 13 drugs (antimicrobials, glucocorticosteroids, anti-inflammatories, anti-hypertensives, anti-cancer drugs and triphenylme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 65 publications
0
14
0
4
Order By: Relevance
“…3). Results showed that the concentrations of anticancer drugs can fluctuate if the sampling was near the hospital or in rural or urban areas (Iglesias et al 2014). Also, results changed according to the Fig.…”
Section: Sample Sourcementioning
confidence: 99%
“…3). Results showed that the concentrations of anticancer drugs can fluctuate if the sampling was near the hospital or in rural or urban areas (Iglesias et al 2014). Also, results changed according to the Fig.…”
Section: Sample Sourcementioning
confidence: 99%
“…Many authors have described the determination of pharmaceuticals in pure, tablet dosage form and real sample using a range of analytical techniques. Analytical techniques including liquid chromatography (LC) and gas chromatography (GC) are commonly employed for the separation and determination of compounds in mixtures, but liquid chromatography is mostly used to determine pharmaceuticals, since they are mostly non-volatile [20,21]. Liquid chromatographic methods for amoxicillin [22], alebendazole [23], chloroquine [24], acetylsalicylic acid [16], caffeine [25], metronidazole [26], theophylline [27] and ciprofloxacin [28] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of pharmaceuticals in different water samples can be performed by various chromatographic techniques, including HPLC–UV [24], HPLC–DAD [25, 26], LC–MS [27], LC–MS/MS [28, 29] and GC–MS [30, 31]. HPLC is the most common method used for separation and determination of these compounds because most pharmaceuticals are non-volatile [12].…”
Section: Introductionmentioning
confidence: 99%
“…As the residue of pharmaceutical compounds is usually present at very low concentrations in the environmental water, a sample preparation and pre-concentration step are necessary before analysis [23, 32]. Several procedures have been reported for the pre-concentration of pharmaceuticals from water matrices including solid phase extraction (SPE) [27, 33], liquid–liquid extraction (LLE) [34], QuEChERS method [35], magnetic solid phase extraction (MSPE) [36], hollow fiber liquid phase microextraction [37] and salting-out assisted liquid–liquid extraction for non-steroid anti-inflammatory drugs (NSAIDs) [38]. Each of these methods has its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%